1997
DOI: 10.12693/aphyspola.92.201
|View full text |Cite
|
Sign up to set email alerts
|

High Quality (100) and (001) Oriented Substrates Prepared from Czochralski Grown SrLaGaO4and SrLaAlO4Single Crystals

Abstract: The growth of SrLaGaO 4 and SrLaAlO4 crystals on (100) and (001) oriented seeds was investigated. Various defects, which appeared in crystals grown on these two orientations, were observed in polarized light and by X-ray diffraction topography. It was found that to obtain a substrate of the best quality, the crystal should be cut along the growth directions. Therefore, crystals pulled along (100) direction are utilized for preparation of (001) substrates, whereas (100) substrates are better to cut from crystal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2005
2005
2010
2010

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 5 publications
1
4
0
Order By: Relevance
“…The synchrotron topographs revealed the misorientation of the crystal lattice inside the "oval" with respect to the rest of the middle region. The elongation of reciprocal space vector along ω direction suggesting the existence of misorientation component was reported in [7,9]. The present topographic studies revealed several misoriented areas.…”
Section: Discussionsupporting
confidence: 79%
See 3 more Smart Citations
“…The synchrotron topographs revealed the misorientation of the crystal lattice inside the "oval" with respect to the rest of the middle region. The elongation of reciprocal space vector along ω direction suggesting the existence of misorientation component was reported in [7,9]. The present topographic studies revealed several misoriented areas.…”
Section: Discussionsupporting
confidence: 79%
“…There are only few papers devoted to the perfection of the SLG crystals, especially with the use of X-ray diffraction methods [7][8][9]. SrLaGaO 4 [7][8][9].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…There are only a few works devoted to the problem of extended crystal lattice defects in SLG [5][6][7]. Yet, many reports on color centers, associated with oxygen-related point defects influencing the color of SLG crystals, can be found in the literature [1].…”
Section: Introductionmentioning
confidence: 99%